Cost of Seizure Disorder Care among Some Selected Patients in Northwestern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Estimated costs of seizure disorder care are overall high due to its high frequency in the general population, especially in developing countries. Considerable variability exists between seizure disorder patients, which poses significant socioeconomic burden to the society.Materials and Methods:A cross-sectional descriptive study with a “bottom-up” design from the societal perspective where information on the costs associated with seizures disorder was evaluated. The direct (medical and non-medical) and indirect (using the “human capital” approach) costs per month for adult outpatients with seizure disorder was estimated. All data were analyzed using IBM SPSS statistics software, version 20.0.Results:The mean healthcare cost per patient per month was N11,096.03 ($58.33). The direct and indirect cost of care per patient per month was N9,004.73 ($45.71) and N2091.30 ($10.62) respectively. The principal direct cost drivers were drugs and other medications amounting to N4041.68 ($20.52) per patient and a total of N371,835.00 ($1887.49) per month for all the patients in the study. The estimated healthcare cost per patient when annualized was found to be N133,152.39 ($675.90), while the total annual healthcare cost for all the patients in the study per year was N12,250,020.00 ($62,182.84).Conclusions:On the background of poor remunerations, high unemployment, and out-of-pocket payments the high costs of care among adults may lead to catastrophic societal expenditures for seizure disorder care, which significantly contribute to poor adherence and secondary treatment gap.